Work-in-Progress--Extracting, Describing and Representing Spatial Features of a Chemical Reaction inside a Virtual Reality Learning Environment - Echeverri-Jimenez, Emmanuel; Oliver-Hoyo, Maria (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
This pilot study provides the preliminary results of a Virtual Reality Learning Environment (VRLE) aimed to increase the two aforementioned skills for chemistry graduate students at NC State. For this purpose, a VRLE was built upon four interconnected frameworks: (1) cognitive apprenticeship, (2) familiar shapes recognition, (3) multimedia design principles, and (4) virtual reality learning affordances. The resource's ultimate goal is to reduce the cognitive load associated with mastering the two target skills. The pilot version of the VRLE was tested by 10 graduate students from the Chemistry Department at NC State University. The students tested the VRLE remotely due to Covid-19. Results are presented for one of the students. This work-in-progress project is the first step towards a student-centered, self-paced, immersive virtual resource complementary to traditional lecture for studying and communicating visually demanding organic reactions.